2018
DOI: 10.1186/s12885-017-3969-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and pathological factors influencing survival in a large cohort of triple-negative breast cancer patients

Abstract: BackgroundTo provide further information on the clinical and pathological prognostic factors in triple-negative breast cancer (TNBC), for which limited and inconsistent data are available.MethodsPathological characteristics and clinical records of 841 TNBCs diagnosed between 1994 and 2015 in four major oncologic centers from Sardinia, Italy, were reviewed. Multivariate hazard ratios (HRs) for mortality and recurrence according to various clinicopathological factors were estimated using Cox proportional hazards… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
48
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 45 publications
(53 reference statements)
9
48
3
Order By: Relevance
“…Regardless of the implications for survival, several groups have shown that the presence of LVSI predicts the development of distant metastatic disease. [21][22][23] Therefore, our results showing LVSI to be independently predictive of distant metastasis in patients without pCR are in accordance with the literature.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Regardless of the implications for survival, several groups have shown that the presence of LVSI predicts the development of distant metastatic disease. [21][22][23] Therefore, our results showing LVSI to be independently predictive of distant metastasis in patients without pCR are in accordance with the literature.…”
Section: Discussionsupporting
confidence: 92%
“…However, not all studies have shown LVSI to influence survival. Urru et al 21 found that LVSI was not significantly associated with survival in multivariate analysis. Regardless of the implications for survival, several groups have shown that the presence of LVSI predicts the development of distant metastatic disease.…”
Section: Discussionmentioning
confidence: 96%
“…However, so far no strong proliferation-based prognosticator specifically for this type of cancer has evolved. We previously found that histopathological subtype serves as an independent prognostic factor, potentially identifying a small subgroup (up to 30% [11][12][13]) of TNBC with a worse prognosis. The present study shows that mitotic counting does not yield any prognostic information for TNBC.…”
Section: Discussionmentioning
confidence: 99%
“…The vast majority of TNBCs is of histological grade 3, while grade 1 TNBCs are rare [11][12][13][14]. It has been suggested, however, that histological grade does not provide prognostic information for TNBC [11,15].…”
Section: Introductionmentioning
confidence: 99%
“…Ovcaricek and coauthors described nodal status and age as independent prognostic factors for disease-free survival (DFS), whereas for overall survival (OS), only nodal status proved to be an independent factor [11]. Urru et al have demonstrated that tumor stage at diagnosis and positive lymph node ratio are relevant predictors of survival and tumor recurrence, with the addition of Ki-67 status for recurrence prediction [12]. Asaga and coworkers have used a different approach, and analyzed clinical response to preoperative systemic chemotherapy [13].…”
Section: Introductionmentioning
confidence: 99%